Multithreading in C♯ 5.0 Cookbook. - Agafonov, Eugene (Packt Publishing, 2013)
Cookbook. Multithreading in C♯ 5.0 Cookbook is written for existing C♯ developers who want a complete, professional, and authoritative guide to multithreading. You don't need any experience with multithreaded programming to use this book.